2020
DOI: 10.3390/cryst10040243
|View full text |Cite
|
Sign up to set email alerts
|

Late Age Dynamic Strength of High-Volume Fly Ash Concrete with Nano-Silica and Polypropylene Fibres

Abstract: The dynamic behaviour of high-volume fly ash concrete with nano-silica (HVFANS) and polypropylene fibres at curing ages of 7 to 90 days was determined by using a split Hopkinson pressure bar (SHPB) machine. At each curing age, the concrete samples were laboratory tested at different temperatures conditions under strain rates reached up to 101.42 s−1. At room temperature, the results indicated that the dynamic compressive strength of plain concrete (PC) was slightly higher than HVFANS concrete at early curing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…With the application of more and more fy ash concrete on high in-situ stress environment, it could be found that the stress wave in high in-situ stress environment led to the failure of fy ash concrete. In recent years, some scholars have begun to study the dynamic mechanical properties of fy ash concrete [19][20][21][22][23]. Zhang et al [24] conducted dynamic splitting tests on concrete with fy ash (contents of 0%, 5%, 10%, 15%, 20%, and 30%) and found that the dynamic splitting tensile strength of concrete with water-cement ratio of 0.45 and 0.6 reaches the maximum value when fy ash content is 10%.…”
Section: Introductionmentioning
confidence: 99%
“…With the application of more and more fy ash concrete on high in-situ stress environment, it could be found that the stress wave in high in-situ stress environment led to the failure of fy ash concrete. In recent years, some scholars have begun to study the dynamic mechanical properties of fy ash concrete [19][20][21][22][23]. Zhang et al [24] conducted dynamic splitting tests on concrete with fy ash (contents of 0%, 5%, 10%, 15%, 20%, and 30%) and found that the dynamic splitting tensile strength of concrete with water-cement ratio of 0.45 and 0.6 reaches the maximum value when fy ash content is 10%.…”
Section: Introductionmentioning
confidence: 99%
“…The environmental problem of concrete can be traced to both existing buildings and structural waste whose useful lives have expired, meaning that they must be recycled or repurposed in significant quantities (Fahmy & Idriss, 2019). Thousands of concrete cubes, cylinders, and prisms are generated every day for laboratory testing or the construction of new buildings (Mussa, Abdulhadi, Abbood, Mutalib & Yaseen, 2020), all of which can also be considered waste material. Numerous researchers have consequently undertaken various studies to determine the practicality of employing re-cycled aggregate concrete (RAC) manufactured from waste concrete in new construction projects.…”
Section: Introductionmentioning
confidence: 99%
“…Engineers quickly started to reuse some of these scrap materials as recycled steel and other metals ingredients in concrete [3]. However, only a small percentage are recycled approximately about 20% to 30% and the remaining is disposed in landfills, causing potentially environmental impacts [4].…”
Section: Introductionmentioning
confidence: 99%